The trophic role and impact of plankton ciliates in the microbial web structure of a tropical polymictic lake dominated by filamentous cyanobacteria - Alfonso Esquivel; Aude Barani; Miroslav Macek; Ruth Ruth Soto-Castor; Celia Bulit (Journal of Limnology, 2016)
The recent interest in the plankton structures and dynamics in tropical and subtropical lakes has revealed important trends that set these lakes apart from temperate lakes, and one of the main differences is the enhanced importance of the microbial food web with respect to net plankton. Ciliates are a key component of subtropical and tropical microbial webs because of their role as dominant picoplankton grazers and their ability to channel picoplankton production to the uppermost trophic levels. Plankton ciliates have been found to play a crucial role in the survival of fish larvae in lakes that share several features with Lake Catemaco, a eutrophic tropical Mexican lake. Therefore, the plankton ciliate composition, abundance, and biomass of Lake Catemaco were studied to assess their role in the microbial food web. The data were obtained from surface and bottom water samples collected at eleven points during three surveys in 2011 and an additional survey in 2013, with the surveys covering the local climatic seasons. The most abundant components of the plankton ciliate assemblages were small prostomatids (Urotricha spp.), choreotrichs (Rimostrombidium spp.), cyclotrichs (Mesodinium and Askenasia), and scuticociliates (Cyclidium, Cinetochilum, Pleuronema, and Uronema). Other important ciliates in terms of abundance and/or biomass were haptorids (Actinobolina, Belonophrya, Monodinium, Paradileptus, and Laginophrya), Halteria, oligotrichs (Limnostrombidium and Pelagostrombidium), Linostomella, Bursaridium, Cyrtolophosis, and Litonotus. The ciliate abundance averaged 57 cells mL-1 and ranged from 14 to 113 cells mL-1. The mean ciliate biomass was 71 µg C L-1 and ranged from 10 to 202 µg C L-1. Differences were not detected in ciliate abundance or biomass between the sampling points or sampling depths (surface to bottom); however, significant differences were observed between seasons for both variables. Nano-sized filamentous cyanobacteria were the most abundant component of the plankton, and their abundance was assessed through epifluorescence microscopy counts. The autotrophic and heterotrophic picoplankton abundance was measured through epifluorescence, and their abundance and biomass were higher at the study site relative to other shallow freshwater ecosystems. The total ciliate biomass distribution patterns were similar to those of filamentous cyanobacteria and autotrophic or heterotrophic picoplankton, although the nanociliate biomasses peaked when the picoplankton and filamentous cyanobacteria were least abundant. The consequences of this increased importance of ciliates on the structure of the plankton at Lake Catemaco will be discussed along with the probable causes.